Differential regulation of collapsin response mediator protein 2 (CRMP2) phosphorylation by GSK3ß and CDK5 following traumatic brain injury - Wilson, Sarah M.; Ki Yeon, Seul; Yang, Xiao-Fang; Park, Ki Duk; Khanna, Rajesh (Frontiers in Cellular Neuroscience, 2014)
Aberrant ion channel function has been heralded as a main underlying mechanism driving epilepsy and its symptoms. However, it has become increasingly clear that treatment strategies targeting voltage-gated sodium or calcium channels merely mask the symptoms of epilepsy without providing disease-modifying benefits. Ion channel function is likely only one important cog in a highly complex machine. Gross morphological changes, such as reactive sprouting and outgrowth, may also play a role in epileptogenesis. Mechanisms responsible for these changes are not well understood. Here we investigate the potential involvement of the neurite outgrowth-promoting molecule collapsin response mediator protein 2 (CRMP2). CRMP2 activity, in this respect, is regulated by phosphorylation state, where phosphorylation by a variety of kinases, including glycogen synthase kinase 3 β (GSK3β) renders it inactive. Phosphorylation (inactivation) of CRMP2 was decreased at two distinct phases following traumatic brain injury (TBI). While reduced CRMP2 phosphorylation during the early phase was attributed to the inactivation of GSK3β, the sustained decrease in CRMP2 phosphorylation in the late phase appeared to be independent of GSK3β activity. Instead, the reduction in GSK3β-phosphorylated CRMP2 was attributed to a loss of priming by cyclin-dependent kinase 5 (CDK5), which allows for subsequent phosphorylation by GSK3β. Based on the observation that the proportion of active CRMP2 is increased for up to 4 weeks following TBI, it was hypothesized that it may drive neurite outgrowth, and therefore, circuit reorganization during this time. Therefore, a novel small-molecule tool was used to target CRMP2 in an attempt to determine its importance in mossy fiber sprouting following TBI. In this report, we demonstrate novel differential regulation of CRMP2 phosphorylation by GSK3β and CDK5 following TBI.